The Lupus-related Lmb3 Locus Contains a Disease-suppressing Coronin-1A Gene Mutation - Haraldsson, M. Katarina (2008)
Here we show that a lupus-suppressing locus is caused by a nonsense mutation of the filamentous actin-inhibiting Coronin-1A gene. This mutation is associated with developmental and functional alterations in T cells, reduced T-dependent humoral responses, and no detectable intrinsic B cell defects. By transfer of T cells it was shown that suppression of autoimmunity could be accounted for by the presence of the Coro1a(Lmb3) mutation in T cells. Our results demonstrate that Coronin-1A is required for the development of systemic lupus and identify actin-cytoskeleton regulatory proteins as potential targets for modulating autoimmune diseases.